2021
DOI: 10.1111/jcmm.16324
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel dysregulated circular RNAs in early‐stage breast cancer

Abstract: Breast cancer is a major cause of cancer‐related death in women worldwide. Non‐coding RNAs are a potential resource to be used as an early diagnostic biomarker for breast cancer. Circular RNAs are a recently identified group of non‐coding RNA with a significant role in disease development with potential utility in diagnosis/prognosis in cancer. In this study, we identified 26 differentially expressed circular RNAs associated with early‐stage breast cancer. RNA sequencing and two circRNA detection tools (find_c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Being the most prevalent form of cancer in women, crucial roles of different circRNAs have been recognized in breast cancer 34 , 127 - 130 , and analyzed through microarray and sequencing techniques 131 . Of the four intrinsic molecular breast cancer subtypes 132 , Triple Negative Breast Cancer (TNBC) is the most aggressive subtype with the highest mortality, increased metastatic spread and limited treatment options 133 , 134 .…”
Section: Functional Mechanisms Of Circrnas Associated With Hippo-yap ...mentioning
confidence: 99%
“…Being the most prevalent form of cancer in women, crucial roles of different circRNAs have been recognized in breast cancer 34 , 127 - 130 , and analyzed through microarray and sequencing techniques 131 . Of the four intrinsic molecular breast cancer subtypes 132 , Triple Negative Breast Cancer (TNBC) is the most aggressive subtype with the highest mortality, increased metastatic spread and limited treatment options 133 , 134 .…”
Section: Functional Mechanisms Of Circrnas Associated With Hippo-yap ...mentioning
confidence: 99%
“…For example, miR-20a, miR-224, miR-383, and miR-378 regulate steroid hormone synthesis in GCs [ 22 , 23 , 24 , 25 ]. miR-1246 has been reported to be an oncogenic miRNA that is involved in the migration and invasion of colon cancer, acute myeloid leukemia, esophageal squamous cell carcinoma, breast cancer, and other cancer cells [ 26 , 27 , 28 , 29 ]. In a preliminary study, we found that kp-10 could decrease miR-1246 expression in BGCs (data unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…For example, circEHD2, circENGLN3, and circNETO2 were found to be upregulated in clear cell renal carcinoma and showed diagnostic and prognostic values ( Frey et al, 2021 ). Recently, Mani et al identified hsa_circ_0006743 and hsa_circ_0002496 to be significantly upregulated in early-stage breast cancer tissues compared to normal samples ( Rao et al, 2021 ). We have previously found that circ_0000745, circ_0001531, and circ_0001640 were upregulated in breast cancer, compared with benign tumor and healthy control ( Wang Y.-W. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%